2010
DOI: 10.1096/fj.09-150714
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α impairs regulation of muscle oxidative phenotype: implications for cachexia?

Abstract: Chronic obstructive pulmonary disease (COPD) is characterized by weight loss, muscle wasting (in advanced disease ultimately resulting in cachexia), and loss of muscle oxidative phenotype (oxphen). This study investigates the effect of inflammation (as a determinant of muscle wasting) on muscle oxphen by using cell studies combined with analyses of muscle biopsies of patients with COPD and control participants. We analyzed markers (citrate synthase, β-hydroxyacyl-CoA dehydrogenase, and cytochrome c oxidase IV)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 103 publications
(58 citation statements)
references
References 55 publications
(11 reference statements)
7
51
0
Order By: Relevance
“…The fold change analysis was followed by a protein network analysis which revealed three distinct functional modules affected by cachexia: Fo complex, electron transport chain, and contractile fibre. Reduced levels of electron transport chain proteins were also reported for skeletal muscles of chronic obstructive pulmonary disease patients 36. Dysregulation of mitochondrial electron transport chain and focal adhesion was also observed by Dahlman and co‐workers in cca patients 32.…”
Section: Discussionsupporting
confidence: 52%
“…The fold change analysis was followed by a protein network analysis which revealed three distinct functional modules affected by cachexia: Fo complex, electron transport chain, and contractile fibre. Reduced levels of electron transport chain proteins were also reported for skeletal muscles of chronic obstructive pulmonary disease patients 36. Dysregulation of mitochondrial electron transport chain and focal adhesion was also observed by Dahlman and co‐workers in cca patients 32.…”
Section: Discussionsupporting
confidence: 52%
“…COPD patients also exhibit high TNF levels in skeletal muscle alongside decreased PGC-1 expression [291]. This repression can be replicated in vitro by chronically treating the C2C12 muscle cell line with TNF The subsequent inhibition of oxidative phosphorylation is dependent on NF-B [291,292].…”
Section: Mutual Influence Of Inflammatory Factors and Pgc-1smentioning
confidence: 98%
“…TNF-a, a downstream target of C/EBP b, has been reported to be associated with neuropathological effects underlying several neurodegenerative disorders (15,16). A substantial amount of evidence has revealed that TNF-a can elicit a wide variety of cellular responses, including profound alterations in transcriptional programs, perturbation of mitochondrial function, production of ROS, enhancement of inflammatory response and apoptosis in a number of cell types (15,(17)(18)(19)(20). In addition, several studies have demonstrated that the suppression of TNF-a production reduces KA-mediated excitotoxicity (21,22); however, it is not yet clear how the C/EBP b-TNF-a signaling axis medi-ates excitotoxic brain damage.…”
mentioning
confidence: 99%